Serological Comparison of the Three Morphological Phases of Coccidioides immitis by the Agar Gel Diffusion Method - Landay, Marshall E. (1967)
Hyperimmune sera against spherules and against arthrospores of Coccidioides immitis were prepared by inoculation of rabbits. The antibody content of these sera was studied by the agar gel diffusion method. It was observed that antispherule pooled sera formed multiple precipitin bands with extracts of spherules and of arthrospores. The antiarthrospore pooled serum, however, failed to precipitate with the spherule extract, and formed a single band in the presence of an arthrospore solution. When the spherule and the arthrospore extracts were tested with a variety of different antisera, it was observed that the spherule preparation formed bands only in combination with anti-purified spherule pooled serum, whereas the arthrospore extract precipitated with anti-purified spherule, antiarthrospore, and anti-Histoplasma capsulatum pooled sera. It was also observed that a spherule culture supernatant solution formed five precipitin bands in combination with anti-spherule pooled sera, formed one band with pooled antiserum from rabbits with coccidioidomycosis, and did not precipitate in the presence of antiarthrospore pooled serum. Coccidioidin, however, formed two bands in the presence of any of these antisera. It was therefore concluded that extracts from the spherule phase of C. immitis differed from solutions obtained from the arthrospore and mycelial phases.